2020
DOI: 10.1007/s11136-020-02699-9
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in adolescents: individual and combined impact of health-related behaviors (DADOS study)

Abstract: Ethics approval. This study was performed in line with the ethical guidelines of the Declaration of Helsinki 1964 (last revision of Fortaleza, Brazil, 2013 and approved by the Research Ethics Committee of the University Jaume I of Castellon (Spain).Consent to participate. Adolescents and their parents or guardians were informed of the nature and characteristics of the study, and all provided a written informed consent. Consent for publication. No applicable.Availability of the data and material. No applicabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 46 publications
(67 reference statements)
9
15
0
1
Order By: Relevance
“…Healthy eating practices are positively related to the HRQoL [ 17 , 40 , 51 ]. In agreement with the previous results, the present study revealed that the adolescents who consumed a better-quality breakfast [ 26 , 27 ], those who consumed all five meals daily [ 52 ], had lunch and dinner with their family [ 49 , 52 ], and those who had optimal AMD [ 21 , 28 , 43 , 49 , 52 , 53 , 54 ] had a better HRQoL. It is known that the higher diet quality that the MD provides, along with other healthy eating habits like breakfast consumption, offers various physical health benefits.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Healthy eating practices are positively related to the HRQoL [ 17 , 40 , 51 ]. In agreement with the previous results, the present study revealed that the adolescents who consumed a better-quality breakfast [ 26 , 27 ], those who consumed all five meals daily [ 52 ], had lunch and dinner with their family [ 49 , 52 ], and those who had optimal AMD [ 21 , 28 , 43 , 49 , 52 , 53 , 54 ] had a better HRQoL. It is known that the higher diet quality that the MD provides, along with other healthy eating habits like breakfast consumption, offers various physical health benefits.…”
Section: Discussionsupporting
confidence: 92%
“…Sex and age were found to be positive predictors of the HRQoL. In this study, similarly to previous findings, the boys [ 21 , 39 , 40 , 41 , 42 , 43 , 44 ] and the younger adolescents [ 39 , 42 , 44 , 45 , 46 ] had a better HRQoL. We expected these findings as sex and age differences in the health-related quality of life are confirmed and could be connected to puberty with all the biological, emotional, and social changes that occur during this period.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In fact, higher academic performance during adolescence has been associated with better earnings [7] and health status later in life [8]. While the relationship of adolescents' health with HRQoL [9,10] and academic performance has been widely investigated [6], how the psychological construct of HRQoL and academic performance are associated is understudied and remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%